On the application of the method of finite spheres to problems in tribology - Macri, Michael; Tichy, John; De, Suvranu (European Journal of Computational Mechanics, 2005)
In this paper we introduce the method of finite spheres, a truly meshfree numerical technique, as a promising scheme for the solution of problems arising in tribology. Some of the attractive features of this technique, contrasted to the traditional finite element methods, include the use of smooth approximation spaces which can be enriched using known asymptotic solutions of the governing partial differential equations as well as the freedom from generation of a complex computational mesh and the need for remeshing for problems involving very large deformations or changes in topology. An elastostatic punch indentation problem is used to showcase the various positive attributes of this method.